When creation and capture diverge: Why breakthrough inventions do not break through alike - Marchesini, Giacomo; Valentini, Giovanni (Strategic Management Journal, 2026)
Abstract Reserch Summary Breakthrough inventions are central to firms' competitive advantage, yet what constitutes a breakthrough remains unclear. We examine the relationship between technological quality (measured by forward citations) and economic value (measured by grant‐day abnormal stock‐returns) of patents. Using U.S. patents assigned to publicly listed firms, we find that among the most exceptional inventions—that is, breakthroughs—the correlation between these two measures disappears: technologically outstanding patents are not necessarily the most economically valuable. We attribute this divergence to a structural tension between value creation and value capture in patenting, driven by novelty, the availability of complementary assets, and competitive dynamics. Firms that successfully manage both dimensions earn a disproportionate market premium. This outcome is often associated with firms that diversify their technological portfolios asynchronously across technology S‐curves. Managerial Summary Breakthrough innovations are widely viewed as the lifeblood of corporate success. Yet what truly defines a breakthrough—and how its value should be assessed—remains unclear. Companies typically rely on two indicators: technological quality (measured by forward citations) and economic value (captured by stock market reactions at patent grant). Conventional wisdom assumes these move together. Our analysis of U.S. patents challenges this view. For the most exceptional inventions, technological quality and economic value diverge. We identify the drivers of this tension and show that firms able to manage it earn disproportionate market returns.